Phosphine‐Catalyzed Enantioselective γ‐Addition of 3‐Substituted Oxindoles to 2, 3‐Butadienoates and 2‐Butynoates: Use of Prochiral Nucleophiles1. Issue 11 (12th February 2014) - Wang, Tianli; Yao, Weijun; Zhong, Fangrui; Pang, Guo Hao; Lu, Yixin
Abstract The first phosphine‐catalyzed enantioselective γ‐addition with prochiral nucleophiles and 2, 3‐butadienoates as the reaction partners has been developed. Both 3‐alkyl‐ and 3‐aryl‐substituted oxindoles could be employed in this process, which is catalyzed by a chiral phosphine that is derived from an amino acid, thus affording oxindoles that bear an all‐carbon quaternary center at the 3‐position in high yields and excellent enantioselectivity. The synthetic value of these γ‐addition products was demonstrated by the formal total synthesis of two natural products and by the preparation of biologically relevant molecules and structural scaffolds.